Environmental Burden Computation in White Crystal Sugar Industry using the Life Cycle Assessment Methods - Hermawan Hermawan; Yulian Syahputri; Kotim Subandi; Adriana Sari Aryani (Journal of Applied Sciences and Advanced Technology, 2020)
Life Cycle Assessment (LCA) is used to assess environmental impacts that can potentially result from an industrial activity, from cradle to grave. LCA assessment in accordance with the principles of ISO 14040 is carried out starting from the stage of determining the scope, collecting data, preparing the Life Cycle Inventory (LCI), formulating the Life Cycle Impact Assessment (LCIA), interpretation and presentation. At the LCI stage, data from a sugar factory studied is collected from the results of material balance analysis, exhaust gas analysis, liquid waste analysis, and solid waste calculations for the 2019 period. Life Cycle Impact Assessment characterizes each LCI data towards potential environmental impacts that are make it possible. Characterization was carried out by grouping the impacts on Energy Depletion Potential (EDP), global warming (GWP), Eco toxicity aquatic (ETA), terrestrial Eco toxicity (ETT), Abiotic Depletion Potential (ADP), Photochemical Oxydant Formation (POF), Acidification Potential (ACP) , Human Toxicity Potential (HTP), Nutrification Potential (NTP), Ozone Depletion Potential (ODP). The fourth largest contribution to the environmental burden of sugar factories based on 2019 data is GWP 375,966.95 tons of CO2 equivalent, followed by ACP 89,183.03 tons equivalent to NOx, EDP worth 33,086.91 tons of fuel oil equivalent, and NTP of 14,598.66 tons equivalent to COD . In addition, it also needs attention, namely HTP 11,621.83 tonnes equivalent to phenol, ETA 11,163.18 tonnes equivalent to BOD5, and ETT 9,748.49 tonnes equivalent to ash.